Highly Tunable Emission by Halide Engineering in Lead-Free Perovskite-Derivative Nanocrystals: The Cs2SnX6 (X = Cl, Br, Br/I, I) System - Veronese, Alessandro; Patrini, Maddalena; Bajoni, Daniele; Ciarrocchi, Carlo; Quadrelli, Paolo; Malavasi, Lorenzo (Frontiers in Chemistry, 2020)
Nanocrystals of Cs2SnX6 (X=Cl, Br, Br0.5I0.5 and I) have been prepared by a simple, optimized, hot-injection method, reporting for the first time the synthesis of Cs2SnCl6, Cs2SnBr6 and mixed Cs2Sn(I0.5Br0.5)6 nanocrystalline samples. They all show a cubic crystal structure with a linear scaling of lattice parameter by changing the halide size. The prepared nanocrystals have spherical shape with average size from 3 to 6 nm depending on the nature of the halide and span an emission range from 444 nm (Cs2SnCl6) to 790 nm (Cs2SnI6) with a further modulation provided by mixed Br/I systems.